Optimization of a Starter Culture for the Production of Quality Yoghurt (Bangladesh Journal of Microbiology, 2018)
Specific microorganisms that determine the body, texture and flavor of final yoghurt is known as starter culture. The present study was carried out to optimize a starter culture for quality yoghurt production. Ten yoghurt samples were collected from different areas of Bangladesh and their organoleptic, biochemical and microbiological properties were assessed to find out the best possible ‘starter’. For optimizing the starter, the effects of different parameters i.e. temperature, pH, incubation time and starter size on the production of quality yoghurt were investigated. After fermentation at different temperatures it was found that 45°C was the best for production of quality yoghurt in six hours, whereas other temperatures needed longer fermentation time. No yoghurt formation occurred within 24 hours at 50°C. This result indicated that at 45°C lactic acid bacteria show higher metabolic activity than the other temperatures. Quality yoghurt was found to be produced at pH ranging from 4.6 to 5 and beyond this pH range quality deteriorated. This study also revealed that both the quality of yoghurt and the fermentation time are dependent on the starter size. Smaller starter size lingers the fermentation period and also produces poor quality yoghurt. It was found that 5% starter was the most suitable one for the production of quality yoghurt. As most yoghurt producers in Bangladesh do not have any advance knowledge about the proper manufacturing conditions of yoghurt production, the output of this study will be helpful for them to produce quality yoghurt.Bangladesh J Microbiol, Volume 34 Number 1 June 2017, pp 27-31